Weak ion sound turbulence and isotope anomaly in electron cyclotron resonance ion source plasmas - Ivanov, A.A.; Serebrennikov, K.S.; Vostrikova, E.A.; Wiesemann, K. (Вопросы атомной науки и техники, 2006)
The production of highly charged ions is very efficient in highly ionized microwave heated plasma in an electron cyclotron resonance ion source (ECRIS). Recent experimental results have revealed that better production of highly charged ions is connected with appearance of weak ion sound turbulence arising due to decay instability of pumping wave in an ECRIS. In some theoretical papers different ions heating due to ion sound turbulence in an ECRIS was studied. Under appropriate conditions due to ion sound turbulence in mixture of two different gases light ions could be heated faster than heavy ions. Since confinement of ions will be the better the lower ion temperature, the differential ion heating enhances losses of preferentially heated light ion component, reducing at the same time losses of the less effectively heated heavy ions. This mechanism appears to be able to explain most of phenomena observed in experiments with “gas mixing effect”. The present article considers the “isotope effect” in an ECRIS plasmas within the model of ion turbulent heating.